Lower and upper Cretaceous paleosols in the western Sichuan Basin, China: Implications for regional paleoclimate. (27th December 2018) - Li, Jun; Wen, Xingyue; Huang, Chengmin
Abstract : Pedogenic features of paleosols preserved in the lower and upper Cretaceous sedimentary strata of the western Sichuan Basin, China, were described and examined in terms of their macromorphology and micromorphology, mineralogy, and geochemistry. These Cretaceous paleosols (entisols, inceptisols, and aridisols) are analogous to modern soil orders based on soil taxonomy (Soil Survey Staff, 2014). A quantitative reconstruction of paleoclimates inferred from the geochemical composition of paleosol horizons, depth to carbonate nodules, and the stable oxygen isotopic composition of pedogenic carbonates in paleosols indicates that a cool‐arid climate associated with short‐term subhumid fluctuations prevailed in the early Cretaceous (Hauterivian) and a cool‐arid climate regime existed in the late Cretaceous (Maastrichtian) of the Sichuan Basin. Atmospheric CO2 concentrations estimated from the paleosol barometer indicated values between 156 ± 138 and 753 ± 339 ppmv for the Hauterivian and between 110 ± 71 and 235 ± 77 ppmv for the middle–late Maastrichtian. An overall coupling between atmospheric pCO2 and paleotemperature occurred in the Sichuan Basin, while the covariations are likely linked to global cooling events in the Maastrichtian and/or are likely associated with the Faraoni oceanic anoxic event (F‐OAE) during the late Hauterivian. Paleoclimate variations in the Sichuan Basin were controlled by regional paleogeography, the prevalence of subtropical high‐pressure systems, monsoonal circulation, and the atmospheric CO2 level in the early and late Cretaceous.